PENGARUH METODE PRAKTIKUM BERBASIS PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR DAN KETERAMPILAN PROSES SAINS SISWA PADA MATERI KELARUTAN DAN HASIL KALI KELARUTAN KELAS XI IPA MAN 2 FILIAL PONTIANAK - Fatimah Fatimah; Mahwar Qurbaniah; Tuti Kurniati (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACTThis study investigated to determine the effect of problem based on practical to the students’learning outcomes and science process skill on Solubility and Solubility Product Constant materials at grade XI of Science class, MAN 2 FILIAL Pontianak. Using pre experimental and one-group pretest post-test designs, this study employed grade XI students of Science class. The data collection technique used were measurement and observation. While the instruments utilized were pre-test, post-test, and science process skill test. The results of learning outcomes analysis of pretest, post-test, and science process skill test by using Wilcoxon (SPSS 17,0 for windos) and run with an alpha level of .05 (5%) revealed that this test rejected Ho and accepted Ha (P value (0,00) < (0,05). The Effect Size (ES) of learning outcomes was 3,53 and considered high. The Z table contributed significant influence of 49,98%. Furthermore, the Solubility Product Constant indicated 2,90 and considered high, as well. The Z table contributed significant influence of 49,81%. As a result there was correlation of problem based on practical to the students’ learning outcomes and science process skill on Solubility and Solubility Product Constant materials.Keywords: learning outcomes, problem based on practical to the students’ learning outcomes, science process skill